STRUCTURE OF MOSS COLONIES IN THE SYOWA STATION AREA, ANTARCTICA (15th Symposium on Polar Biology) - イムラ, サトシ; ヒグチ, マサノブ; カンダ, ヒロシ; イワツキ, ゼンノスケ; IMURA, Satoshi; HIGUCHI, Masanobu; KANDA, Hiroshi; IWATSUKI, Zennoske (National Institute of Polar Research, 1994)
P(論文) The morphological structure of colonies in vertical section was investigated for Bryum argenteum, B. pseudotriquetrum and Ceratodon purpureus in the Syowa Station area, Antarctica. The colonies of these species were composed of two layers: shoot layer containing green shoot tips and brownish shoots and rhizoid layer containing rhizoids and disrupted plant materials. The colonies of B. argenteum were shallower than those of other Antarctic mosses, and also those of B. argenteum in Japan. The depth of the rhizoid layer of all three mosses were almost the same, but the shoot layer of B. argenteum in Antarctica was very shallow. In some cases, B. argenteum and B. pseudotriquetrum were found in the same colonies. Three structural patterns were recognized in the arrangement of two soecies in the same colonies. departmental bulletin paper